ELITE LOKAL YANG BERBASIS PESANTREN DALAM KONTESTASI PEMILIHAN KEPALA DAERAH JAWA TIMUR - Abdul Chalik (Karsa: Journal of Social and Islamic Culture, 2015)
This article examines the results of local elections of East Java in 2015 and involvement of pesantren (Islamic boarding school)-based local elites, namely kiai (Islamic venerated schoolar) and santri (Islamic student), in winning some of regents/mayors. As an illustration that the local elections simultaneously in 19 districts/municipalities in East Java, 16 of which were won by incumbents. Power of incumbents not only lies in powers of networking and funding, but also the support of the pesantren-based local elites (kiai and santri). In perspective of Powercube theory, existence of the local elites is not only in the visible power, but also in the hidden power and the invisible power. Similarly, spaces they have played are not only in the invited spaces, but also in the closed spaces. However, not much has entered the created spaces or third spaces. In the space and the existence of the power, the pesantren-based local elites in synergy with the political power, especially in support of the Incumbents who are fighting to retain power. In local politics, the role of pesantren-based local elites increasingly evident, because they directly intersect with the interests of their respective regions. As a result of direct involvement, the collision and friction are inevitable.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.744